Building Better Digital Badges: Pairing Completion Logic With Psychological Factors. (February 2016) - McDaniel, Rudy; Fanfarelli, Joseph
Background. Digitalbadges are used in games and simulations for purposes such asincentivizing learning, identifyingprogress, increasingtime on task, andcredentialing . Designing effective badges is complicated bypsychological factors mediating the processes of recognizing, orienting toward, and acquiring badges. Aim. This article analyzes digital badges throughmechanics andpsychology . This approach involves understanding the underlyinglogics of badges as well as theexperiential nature of badges-in-use. The proposedmodel provides additional insight about badges and recommendsdesign strategies to complement existing scholarship. Procedure. This article examines an existing model ofcompletion logic for digital badges. This model is expanded upon by pairing these formal mechanics with relevantpsychological theory, summarizing keyprinciples that pertain to how peopleinteract with badges. It then considers threedimensions of badges-in-use—social, cognitive, and affective—reviewing examples and analyzing the relationship of badging to debriefing. Outcome. Understanding the relationships betweenformal completion logics and the psychologicalexperience of badging allows designers to better design, deploy, and critique badging systems, leading to moreeffective implementations within simulation and gaming contexts. Adesign matrix and a series of designrecommendations for badging are derived from the presented perspectives.